Describing the Educational Journey of Bachelor of Secondary Education Major in English Students - Trishia Cesar Patalinghug; Rud Ghyne Montealto; Aris Pet Angeli Suarez; Genesis Naparan (Journal of English as A Foreign Language Teaching and Research, 2025)
This qualitative study explores the educational experiences of Bachelor of Secondary Education (BSED) students majoring in English, focusing on their motivations, expectations, challenges, and coping strategies. This study addresses the phenomenon of students dealing with challenging educational programs while desiring to develop the abilities essential for effective teaching. This section aims to understand the factors influencing their decision to pursue this program, the skills they develop, and how they overcome academic and personal obstacles. Semi-structured interviews were conducted with 14 BSED English students, two English teachers, and two peers. Using thematic analysis, recurring themes and patterns were identified. Results reveal that students were driven by job opportunities, family and social influences, and personal interests. They expect to improve their speaking skills, language proficiency, and teaching strategies. Challenges include low self-esteem, teacher incompetence, and academic difficulties, while coping mechanisms involve using online resources, seeking support, and practicing self-directed learning. This study emphasizes the importance of personal and academic support systems in fostering student resilience and offers recommendations for aspiring students, such as cultivating a passion for teaching, engaging in collaborative learning, and adopting strategic reviewing.